Enhancing Awareness of Early Marriage through Video Media: A Study in Cirebon Junior High Schools - Yuhandini, Diyah Sri; Jubaedah, Entin; Sriyatin, Sriyatin (Universitas Tribhuwana Tunggadewi, 2024)
Child marriage is a pervasive global problem that has a significant impact on numerous countries across the globe. The objective of this study is to analyze the disparities in knowledge and attitudes among junior high school students in Cirebon in 2023, before and after an intervention using audiovisual media to raise awareness about the hazards of early marriage. This study utilized a quantitative approach and incorporated a quasi-experimental methodology known as the one-group pretest-posttest design. The sampling method was purposive sampling, specifically targeting kids from thirteen junior high schools in Cirebon, with a total of 204 participants. The study findings suggested a significant improvement in knowledge following the session. During the pretest, 87 students, accounting for 42.6% of the total, demonstrated good knowledge. This number increased to 137 students, or 67.2%, in posttest-1, and further to 197 students, equivalent to 96.6%, in posttest-2. In the pretest, 98 students (48%) demonstrated a positive attitude towards recognizing the risks of early marriage. This percentage climbed to 108 students (52.9%) in posttest-1 and further to 188 students (92.2%) in posttest-2. The statistical analysis using Cochran's test revealed a p-value of 0.00 for both knowledge and attitude, demonstrating substantial disparities in knowledge and attitudes before the intervention, after the first intervention, and after the second intervention about the hazards of early marriage.